The Millennium Development Goals Report 2012 - United Nations (New York United Nations, 2012)
This year?s report on progress towards the Millennium Development Goals (MDGs) highlights several milestones. The target of reducing extreme poverty by half has been reached five years ahead of the 2015 deadline, as has the target of halving the proportion of people who lack dependable access to improved sources of drinking water. Conditions for more than 200 million people living in slums have been ameliorated?double the 2020 target. Primary school enrolment of girls equalled that of boys, and we have seen accelerating progress in reducing child and maternal mortality
Keywords: Millennium Development Goals, Health Education Mortality Sanitation